Aplikasi Konversi Angka Ke Satuan Menggunakan Kamera Smartphone Berbasis Android - sarti, kiki yustika; Suwardoyo, Untung (Fakultas Teknik Universitas Muhammadiyah Parepare, 2022)
In education, especially for Elementary School, precisely in grade 2 in mathematics, students learn one conversion, namely unit conversion. In calculating unit conversion, students often find it difficult to complete it. In the problems found, the main problem contained in this research is how to make an application program that can make it easier for students to complete unit conversion calculations using smartphones, by means of the camera taking pictures of numbers and then converting them into text and then converting them to the same units. The Image Processing method applied to the use of this application can display unit conversion results by simply highlighting a number image using the Android camera. Based on the results of the research conducted, the research results obtained in the form of limitations of image processing where from 12 unit conversion processes the results obtained the application accuracy rate was able to convert units of 100%, but in the image to text process the results of an accuracy rate of 85% this was caused by several factors include the quality of the detected image and the inadequate lighting factor.